Accounting control and controlling accounting : interdisciplinary and critical perspectives - Broadbent, Jane; Laughlin, Richard (Emerald, 2013)
"This book advocates and illustrates the use of Interdisciplinary and Critical Perspectives on Accounting as a means to analyse Accounting Control at a societal level and to show how accounting is 'regulated' within organisations. Interdisciplinary and Critical Perspectives on Accounting derives from a view that accounting is not part of and should not be exclusively viewed from a neo-classical economics perspective, but, rather, should be informed and analysed from alternative social science perspectives. The book provides an illustration of the power of this thinking to analyse two key broad areas of accounting involvement in societies and organisations, which can be referred to as 'accounting regulation' and the 'regulation of accounting'"--EBL.